The influence learning used ABC run exercise on the sprint capabilities - Akhmad Sobarna; Sumbara Hambali; Sutiswo Sutiswo; Denok Sunarsi (Jurnal Konseling dan Pendidikan, 2020)
The purpose of this research is to know Influence of Learning through ABC Run Training to ability of sprint. This research uses quasy experimental research method with Pretest - Posttest Control Group Design Design. The population of this research is students, sample determination is done by cluster random sampling technique, then got two class which used as control group and experiment group. The instrument used is through direct observation based on the criteria of the basic engineering assessment which has been provided. After the processing and data analysis, the final test result showed that the control group did not experience significant change, while the experimental group experienced significant change of test result. Based on the results of hypothesis testing it can be concluded that learning through exercise ABC Run has a significant influence compared to learning without through ABC Run training on the sprint capabilities.